Effectiveness of Molasses, Washed Rice Water, and Coconut Water in Baglog Media on Production of White Oyster Mushroom (Pleorotus ostreatus) - Ali, Fahri; Yeni, Yeni; Rahhutami, Ratih; Darma, Wika Anrya; Sesanti, Rizka Novi (abe.fp.unila.ac.id, 2023)
Pleourotus ostreatus, well known as an white oyster mushroom is the most popular edible mushroom in Indonesia. Baglog (sawdust as main substrat) is usually used to cultivating them. In the cultivation, it often occurs that the growing media in the baglog is not able to support the growth of oyster mushroom optimally. It is possible to add some supplements in the middle of cultivation period. The study aims to obtain information on the potential of molasses, washed rice water, and coconut water as nutritional supplements in white oyster mushroom cultivation to increase the production of it. This research was conducted from August to December 2022 at mushroom plant house (kumbung), Lampung State Polytechnic. This research used descriptive method with couple of parameter, like yield and form of white oyster mushroom. The results of this study shown that washed rice water can be used as supplement materials and has given the highest of white oyster mushroom yield (90.008 g). followed by coconut water (63.661 g), and molasses (51.102 g). On the other hand, the addition of washed rice water affect in productivity period if compared to molasses and coconut water addition.